II)Dividing the equation by "xy^2" , we have "\\frac{(yz+z^2)dx}{xy^2}+\\frac{ydz-zdy}{y^2}=0" . Since "\\frac{ydz-zdy}{y^2}=d\\bigl(\\frac{z}{y}\\bigr)" , we can rewrite the equation: "\\bigl(\\frac{z}{y}+\\bigl(\\frac{z}{y}\\bigr)^2\\bigr)\\frac{dx}{x}+d\\bigl(\\frac{z}{y}\\bigr)=0" . After making change of the variables "\\frac{z}{y}=t" , we have "(t+t^2)\\frac{dx}{x}+dt=0" or "\\frac{dx}{x}=-\\frac{dt}{t+t^2}=\\frac{dt}{t+1}-\\frac{dt}{t}" . Solution of this equation is "\\ln |x|+C=\\ln |t+1|-\\ln |t|=\\ln\\bigl |\\frac{t+1}{t}\\bigr|" . Rewrite this equaliy: "e^c|x|=\\bigl|\\frac{t+1}{t}\\bigr|" . That is "e^cx=\\frac{t+1}{t}" or "-e^cx=\\frac{t+1}{t}" . Union of these 2 cases is "Dx=\\frac{t+1}{t}" . Remembering that "t=\\frac{z}{y}" , we have "Dx=\\frac{y+z}{z}"
Answer: "Dx=\\frac{y+z}{z}"
III)Rewrite the equation: "(z+z^3)(\\cos xdx-dy)+(1-z^2)(y-\\sin x)dz=0" . Note that "\\cos xdx-dy=d(\\sin x-y)" .
So after making change of the variables "\\sin x-y=t" , we have "(z+z^3)dt-(1-z^2)tdz=0" or "\\frac{dt}{t}=\\frac{(1-z^2)dz}{z+z^3}"
"\\frac{1-z^2}{z+z^3}=\\frac{A}{z}+\\frac{Bz+C}{z^2+1}=\\frac{A(z^2+1)+z(Bz+C)}{z^3+z}=\\frac{(A+B)z^2+Cz+A}{z^3+z}" , so "\\begin{cases}\nA+B=-1\\\\\nC=0\\\\\nA=1\n\\end{cases}" , where "A=1, B=-2, C=0"
We have "\\frac{1-z^2}{z+z^3}=\\frac{1}{z}-\\frac{2z}{z^2+1}" . Since "\\frac{dt}{t}=\\frac{dz}{z}-\\frac{2zdz}{z^2+1}" , we have "\\ln |t| = \\ln |z| - \\ln |z^2+1| +C" or "|t|=e^C\\bigl|\\frac{z}{z^2+1}\\bigr|" . That is "t=e^C\\frac{z}{z^2+1}" or "t=-e^C\\frac{z}{z^2+1}" . Union of these 2 cases is "t=D\\frac{z}{z^2+1}" . Remembering that "t=\\sin x-y" , we have "\\sin x-y=D\\frac{z}{z^2+1}"
Answer: "\\sin x-y=D\\frac{z}{z^2+1}"
Comments
Leave a comment